Criminalising dissent : lèse-majesté and the path to autocracy - Kurtul, Aytekin Kaan (Routledge, 2025)
"This book addresses one of the oldest political offences in the European continent, lèse-majesté, in light of its historical evolution and the threat it poses to a democratic public sphere in modern-day Europe. The Republic of Turkey, which serves as the focal point of this book, epitomises the "chilling" (ab)use of lèse-majesté laws due to the sheer number of criminal investigations on the basis of lèse-majesté as well as the relatively low threshold for permissible criticism in defamation cases concerning the head of state. In this regard, through a comparative analysis encompassing multiple European jurisdictions and international human rights law, this work illustrates that the excesses in Turkey should not be treated as an alien practice, but rather as a caution for liberal political systems in Europe in view of the Western European origins of Turkish lèse-majesté and the erosion of the rule of law. Thus, the volume stands as both a warning and a call for the abolition of lèse-majesté laws as a democratic necessity beyond their inherent contradiction with state obligations stemming from international human rights law. As a comprehensive work on European lèse-majesté, this book will function as a point of reference for legal scholars and practitioners alike, as it offers a historical and theoretical background in addition to its rich commentary on how lèse-majesté cases are assessed by domestic criminal courts and international human rights bodies. The book will also be of use to political scientists and journalists who wish to learn more about how heads of state can effectively become immune to criticism through the use of criminal law, and what can be done when faced with a lèse-majesté charge for doing one's job"--